Preparation and application of rose oil capsules onto printable paper - ÖZCAN, ARİF; ARMAN KANDIRMAZ, EMİNE (My University, 2022)
In this study, rose oil was encapsulated with stearic acid substituted polyvinyl alcohol macromolecule. In the first part of the study, stearic acid substituted polyvinyl alcohol macromolecule was synthesized and its chemical structure was elucidated by ATR-FTIR and ¹HNMR. Then, rose oil was encapsulated using this obtained polymer. The chemical structure of the obtained capsules was made by ATR-FTIR, and dimensional analysis was done by scanning electron microscope (SEM). After the obtained capsules, a paper coating formula was prepared and coated on 80 g/m² paper. The resulting scented papers were printed using the screen printing technique. The color, gloss, and deformation of the capsules on the surface of the printed and unprinted papers were determined by spectrophotometer, glossmeter and SEM. As a result, it was determined that the synthesized polymer could encapsulate the rose oil and the papers using these capsules could be printed without deformation.
Keywords: Tarımsal Bilimler; Ormancılık; Orman Endüstri Mühendisliği; Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Forestry; Forest Industry Engineering; Metallurgical and Materials Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Bitki ve Hayvan Bilimleri; Malzeme Bilimi; ORMANCILIK; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); PLANT & ANIMAL SCIENCE; MATERIALS SCIENCE; FORESTRY; METALLURGY & METALLURGICAL ENGINEERING; Yaşam Bilimleri; Life Sciences; Printability; encapsulation; rose oil; coating